The Use of Two Potassium Sources on the Growth and Production of Sweet Potato (Ipomoea batatas) in Inceptisol - Hapsoh, Hapsoh; Suwantua- T, Boni Vasius; Yoseva, Sri (JURNAL BUDIDAYA PERTANIAN, 2023)
Production of sweet potatoes in Riau Province has decreased from 9,667 tons in 2018, 8,021 tons in 2019, to 7,305 tons in 2020, due to a decrease in harvested area of 490 ha in 2018, 483 ha in 2019, and 371 ha in 2020. To increase production, efforts that can be done is by expanding the planting area by utilizing Inceptisol soil. However, Inceptisol soil has constraints in terms of its chemical and physical properties. Effort to develop sweet potatoes in Inceptisol soil is by using empty fruit bunch (EFB) ash which is a source of potassium, although farmers usually use inorganic potassium fertilizer (KCl). This research aims to determine the effect of using two sources of potassium on the growth and production of sweet potato. The research used a non-factorial completely randomized design with 5 treatments, KCl 100 kg/ha, KCl 125 kg/ha, EFB ash 1000 kg/ha, EFB ash 2000 kg/ha and EFB ash 3000 kg/ha. The data obtained were analyzed statistically using analysis of variance followed by Duncan's multiple range test at a 5% significance level. The results showed that the application of EFB ash 1000-2000 kg/ha can increase sweet potato in Inceptisol by increasing tuber weight per 2.45 m2.